2021
DOI: 10.2147/oaem.s310932
|View full text |Cite
|
Sign up to set email alerts
|

Emergency and Disaster Handling Preparedness Among Front Line Health Service Providing Nurses and Associated Factors at Emergency Department, at Amhara Regional State Referral Hospitals, Ethiopia

Abstract: Introduction Globally around 1.6 million individuals have died as a result of disasters per year. These disruptive events that happen in the world each day result in damage to individuals, families, and communities. Methods An institution-based cross-sectional study was conducted. All frontline health-care providers at the emergency departments of Amhara Regional State Referral Hospitals during the study period were considered as studied subjects. Data were collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…Level of knowledge towards disaster risk management : This study showed that 171(64%) of the participants had poor level of knowledge regarding disaster risk management, which is supported by reports of studies done in Amhara regional state and AA public hospitals ( 7 , 22 ). However, it is different from a similar study in Saudi Arabia and Jimma Zone, Ethiopia ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Level of knowledge towards disaster risk management : This study showed that 171(64%) of the participants had poor level of knowledge regarding disaster risk management, which is supported by reports of studies done in Amhara regional state and AA public hospitals ( 7 , 22 ). However, it is different from a similar study in Saudi Arabia and Jimma Zone, Ethiopia ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 74%
“…Around 1.6 million people have died because of disasters in the world that is approximately 65,000 deaths annually, and trillions of dollars in related damages have been lost, since 1990. Disasters are able to change the appearance of a developing nation suddenly and may collapse their years of achievement ( 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other studies conducted in the USA, Northwest Arkansas, Iran, Indonesia, Egypt, and Ethiopia. 13,1620 As nurses and physicians are frontline employees in the emergency room, this data suggests that their familiarity with emergency and disaster preparedness is inadequate. The increasing number of mass casualties necessitates more significant attention to improving the competencies of these frontline health care workers in emergency preparedness through various strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This creates a vicious cycle of disaster and emergency events for Ethiopia and the African continent. 6 Despite Ethiopia’s double-digit economic growth over the last ten years, urban disasters, such as fire and other incidents, are rising due to urbanization. 7 Unlike in the past, besides drought, the risk of other disasters like floods, landslides, human epidemics, crop pests, forest and bushfires frequency, scale, and intensity of such disasters have been increasing due to different factors, including climate change.…”
Section: Introductionmentioning
confidence: 99%